Limit analysis of vaulted structures strengthened by an innovative technology in applying CFRP. (1st August 2017) - Anania, Laura; D'Agata, Giuseppe
Highlights: A new approach to lower bound limit analysis of CFRP reinforced masonry arch is discussed. The basic idea of the proposed approach is to carry out a series of lower bound limit analysis. The shear strength is constant and given by the Mohr-Coulomb friction law from the previous step. The methodology results in very good agreement with available original experimental data. Abstract: Masonry vaults represent one of the most seismic vulnerable element in an ancient building. It also generally does not possess an adequate capability of redistribution of the seismic action among the walls of the buildings. Nowadays the preservation of the historic vaults is devolved to the application of advanced materials and new technologies on traditional structures. The evaluation of their effects has assumed a major relevance. From the analytical point of view, the plastic (limit) analysis methods are now commonly used to determine the ultimate load–carrying capacities of masonry arch The aim of the present paper is to discuss the efficiency of an analytical models validated by means of experimental investigations carried out on masonry arches reinforced with an innovative technology proposed by the same author and based on the use of CFRP strips, with a special configuration called as "Ω-wrap". This configuration allows the resulting CFRP reinforced ribbed vault to assume the necessary strength and membranal and flexural rigidity so as to ensure the aforementioned seismic action redistribution capability and to avoid local collapse of the vault. A theoretical prediction of ultimate strength was derived in agreement with the occurrences observed during the experiments (masonry crushing, FRP rupture, debonding, sliding along the mortar joint). To this aim, a novel incremental step-by-step lower bound limit analysis approach was developed taking into account for the shear failure mechanism at each mortar joint. The shear strength is evaluated by the Mohr-Coulomb friction law for the mortar joint and by other nonlinear Italian Code relations for CFRP Ω-Wrap reinforcement. In the approximated incremental analysis process the current value of the shear strength, depend on the compressive stress resulting from the previous step.